2011
DOI: 10.1021/ct2002013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Popular DFT and Semiempirical Molecular Orbital Techniques for Calculating Relative Transition State Energies and Kinetic Product Distributions in Enantioselective Organocatalytic Reactions

Abstract: The performance of computationally accessible levels of calculation for the transition states of organocatalytic reaction has been assessed. Reference post-Hartree-Fock single point energy calculations were used as standards for the gas-phase Born-Oppenheimer relative energies of pairs of alternative transition states that lead to the two product enantiomers. We show that semiempirical methods cannot even be relied on to yield qualitatively correct results. The geometries (optimized, for instance, with DFT) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…The results are summarized in Table 1, from which it can be concluded that the best correlation between the benchmark CCSD(T)/def2‐QZVP+COSMO‐RS23 values and the tested DFT functionals was obtained for the ωB97xd/cc‐pVTZ method in combination with the SMD24 solvation model (Table 1). In line with the studies by Clark and Tsogoeva,23e performing the geometry optimization with the ωB97xd/cc‐pVDZ method turned out to afford a better correlation with the CCSD(T) data than that attained by using the B3LYP/6‐31 g(d,p) method (compare methods A and D , Table 1). Therefore, (ωB97xd/cc‐PVTZ+SMD)//(ωB97xd/cc‐PVDZ+SMD) was employed as the method of choice for further calculations.…”
Section: Resultssupporting
confidence: 76%
“…The results are summarized in Table 1, from which it can be concluded that the best correlation between the benchmark CCSD(T)/def2‐QZVP+COSMO‐RS23 values and the tested DFT functionals was obtained for the ωB97xd/cc‐pVTZ method in combination with the SMD24 solvation model (Table 1). In line with the studies by Clark and Tsogoeva,23e performing the geometry optimization with the ωB97xd/cc‐pVDZ method turned out to afford a better correlation with the CCSD(T) data than that attained by using the B3LYP/6‐31 g(d,p) method (compare methods A and D , Table 1). Therefore, (ωB97xd/cc‐PVTZ+SMD)//(ωB97xd/cc‐PVDZ+SMD) was employed as the method of choice for further calculations.…”
Section: Resultssupporting
confidence: 76%
“…The merits of ωB97X-D in organocatalytic modeling have also been established in an extensive benchmark study by Clark and co-workers [78]. …”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) methods represent a viable alternative for elucidating the kinetics and mechanisms of atmospheric chemistry processes, due to their excellent performance‐to‐cost ratio . Thus far, many functionals have been developed, each with merits and drawbacks.…”
Section: Introductionmentioning
confidence: 99%